Hospital based randomized prospective study outcomes in colorectal surgery after bowel preparation - Bhat, Altaf Hussain; Mir, Gh Hussain; Bhat, Sajad Ahmad; Ali, Muzaffar (International Surgery Journal, 2020)
Background: Research of so many years from the procurable world data has shown that the reasons for most colorectal cancers occur due to change in life style the type of diet, smoking as well as the influence of the surrounding environment in which man lives and increasing age with only a minority of cases associated with genetic disorders. Colorectal cancer is the third most commonly diagnosed cancer. In the first half of the 20th century, mortality from colorectal surgery often exceeded 20%, mainly attributed to sepsis. Methods: The randomized prospective study was conducted on 202 colorectal cancer patients in the department of Colorectal division of General and Minimal Invasive surgery” Sher-i-Kashmir Institute of Medical Sciences, Srinagar. Results: Mean age of patients in Group 1 (with no mechanical bowel preparation (NMBP)) was 51±18.15 years while as same was 50±17.76 years for Group 2 (with mechanical bowel preparation (MBP)). Age range for Group 1 was 16-87 years and16-85 years for Group 2. Regarding outcomes, wound infections were 6.1% and 3.8% in Group 1 and Group 2 respectively. While disruption of anastomosis were 2.0% and 3.8% in group A and B respectively. Conclusions: Statistically no gross difference in terms of morbidity and mortality was found between the use of mechanical bowel preparation versus no use of mechanical bowel preparation in elective colorectal surgery. Elective Colorectal Surgery can safely be performed without enduring MBP in it as it does not possess any sorts of benefits.